Mutations in PTRH2 cause novel infantile‐onset multisystem disease with intellectual disability, microcephaly, progressive ataxia, and muscle weakness. (3rd December 2014) - Hu, Hao; Matter, Michelle L.; Issa‐Jahns, Lina; Jijiwa, Mayumi; Kraemer, Nadine; Musante, Luciana; de la Vega, Michelle; Ninnemann, Olaf; Schindler, Detlev; Damatova, Natalia; Eirich, Katharina; Sifringer, Marco; et al.
Abstract Objective To identify the cause of a so‐far unreported phenotype of infantile‐onset multisystem neurologic, endocrine, and pancreatic disease (IMNEPD). Methods We characterized a consanguineous family of Yazidian‐Turkish descent with IMNEPD. The two affected children suffer from intellectual disability, postnatal microcephaly, growth retardation, progressive ataxia, distal muscle weakness, peripheral demyelinating sensorimotor neuropathy, sensorineural deafness, exocrine pancreas insufficiency, hypothyroidism, and show signs of liver fibrosis. We performed whole‐exome sequencing followed by bioinformatic analysis and Sanger sequencing on affected and unaffected family members. The effect of mutations in the candidate gene was studied in wild‐type and mutant mice and in patient and control fibroblasts. Results In a consanguineous family with two individuals with IMNEPD, we identified a homozygous frameshift mutation in the previously not disease‐associated peptidyl‐tRNA hydrolase 2 (PTRH2) gene. PTRH2 encodes a primarily mitochondrial protein involved in integrin‐mediated cell survival and apoptosis signaling. We show that PTRH2 is highly expressed in the developing brain and is a key determinant in maintaining cell survival during human tissue development. Moreover, we link PTRH2 to the mTOR pathway and thus the control of cell size. The pathology suggested by the human phenotype and neuroimaging studies is supported by analysis of mutant mice and patient fibroblasts. Interpretation We report a novel disease phenotype, show that the genetic cause is a homozygous mutation in the PTRH2 gene, and demonstrate functional effects in mouse and human tissues. Mutations in PTRH2 should be considered in patients with undiagnosed multisystem neurologic, endocrine, and pancreatic disease.